Epidemiological study on artistic gymnastics injuries - De Vita, M.; Panetta, V.; Prattico, F.; Foti, C. (Medicina dello Sport, 2015)
Aim. The aim of this present study was to investigate the prevalence of gymnastics' injuries related with gear training and level of Artistic Gymnastic athletes (AGA).